ChemInform Abstract: Synthesis of Isoxazolin‐5‐one Glucosides by a Cascade Reaction. Issue 23 (10th June 2014) - Becker, Tobias; Goerls, Helmar; Pauls, Gerhard; Wedekind, Roland; Kai, Marco; von Reuss, Stephan H.; Boland, Wilhelm
Abstract A new and efficient approach to the natural sugar derivative (VI) and its α‐isomer (V) is reported.